The Impact of Sequential Multilingualism on Self-Perceived Personality Shift: The Case of Master One EFL Students at M’sila University - Ms. Menel NIA; Mr. Younes KOUDRI (UNIVERSITY OF MOHAMED BOUDIAF- M’SILA, 2025)
ABSTRACT In the context of bilingualism and simultaneous multilingualism, many studies have examined the phenomenon of personality shift, but only a few were conducted on sequential multilinguals, and fewer investigated the impact of social context on the phenomenon. This study aims to explore whether sequential multilinguals perceive a shift in their personality traits when using a foreign language and the influence of different social contexts on these perceptions. The study adopted a mixed-method approach with an exploratory design in nature, and implemented descriptive method, using an embedded design questionnaire with both scaled and open-ended questions with an adaptation of the Big Five Inventory. The participants of the study (n=64) were Master One EFL students at M’sila University, and their answers were statistically analyzed and thematically coded concerning the open-ended responses. The findings of the study showed that participants perceived notable personality shifts in agreeableness and openness when using SL/FL compared to L1, while other traits, which are neuroticism and extraversion were moderately affected. Moreover, social contexts were found to play a role in how personality traits were expressed. This study supports the notion that personality traits are dynamic and provides insights on sequential multilinguals’ percieved personality shift when they use SL/FL, and the impact of social contexts of traits manifestation.
Keywords: Keywords: Language Acquisition; Sequential Multilingualism; Multilingual Personality; Language and Identity; Social Context; Personality Shift; The Big Five Personality Model